PENGARUH FREE CASH FLOW, RISIKO BISNIS, DAN KEBIJAKAN UTANG TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Ni Kadek Dwi Suciati; I Wayan Widnyana; Gregorius Paulus Tahu (VALUES, 2021)
Firm value is an indicator of how the market values ​​the company as a whole. Firm value is very important because it reflects the company's performance which can affect investors' perceptions of the company. This study aims to test and obtain empirical evidence of the effect of free cash flow, business risk, and debt policy on firm value in manufacturing companies listed on the Indonesia Stock Exchange. The population in this study are manufacturing companies listed on the IDX in 2016-2018. The sample in this study were 12 manufacturing companies which were determined based on the purposive sampling method. The data analysis technique used in this study is multiple regression analysis. The results showed that free cash flow had a positive and significant effect on firm value. Business risk has a negative and significant effect on firm value. Debt policy has a positive and significant effect on firm value at the company. Further research is also suggested to conduct research on companies with more diverse characteristics, so that the results obtained can represent a conclusion by comparing each sector of companies listed on the Indonesia Stock Exchange.